2001
DOI: 10.1002/hed.1081
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a concomitant chemotherapy and radiotherapy regimen for squamous cell head and neck cancer: A systematic review of the published literature with subgroup analysis

Abstract: Platinum-based concomitant CT and RT is superior to conventional RT alone in improving survival in locally advanced SCHNC. Subgroup analyses can be used to help in choosing the most appropriate concomitant regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(154 citation statements)
references
References 47 publications
0
153
0
1
Order By: Relevance
“…26,27 Hence, we next sought to investigate the regulation of chemokine receptors on tumor cells, during the exposure to this antineoplastic agent. CXCR4-expressing ACC cells were exposed to sublethal doses of cisplatin at the concentrations of 1, 3 and 9 lg/ml.…”
Section: The Antineoplastic Agent Cisplatin Upregulates Cxcr4 On Tumomentioning
confidence: 99%
“…26,27 Hence, we next sought to investigate the regulation of chemokine receptors on tumor cells, during the exposure to this antineoplastic agent. CXCR4-expressing ACC cells were exposed to sublethal doses of cisplatin at the concentrations of 1, 3 and 9 lg/ml.…”
Section: The Antineoplastic Agent Cisplatin Upregulates Cxcr4 On Tumomentioning
confidence: 99%
“…Recently, Browman et al 17 reported a metaanalysis including 18 trials with 3,192 patients, in which concurrent chemotherapy-radiation therapy was compared to radiation therapy alone (Table 3). Overall, the chemotherapy-radiation therapy arm was again superior to radiation therapy alone (P<.00001).…”
Section: Locally Advanced Resectable Cancermentioning
confidence: 99%
“…Patients with unresectable disease usually undergo CCRT; the 3-year OS rates of CCRT with cisplatin-based chemotherapy were reported to be 20-30% (1-3). Although CCRT is superior to radiotherapy alone in improving survival, increasing toxicity must be considered (20,21). To improve treatment outcomes, CCRT with S-1 was administered to patients with advanced oral SCC.…”
Section: Discussionmentioning
confidence: 99%